The Impact and Influence of Social Media on Consumer-Brand Relationship : Case Study In Health Product Brands - Ning, Jing (2017)
Purpose: This study aims to analyze the impact and influence of several brand related factors (i.e., brand experience, brand attribute, brand familiarity, endorser effect, online advertisement and social media) on consumer-brand relationship.